Impact of Mild Traumatic Brain Injury on the Subjective Perception of Hearing and Balance - Civantos, Alyssa M.; Johnson, Kennedy; Azzawi, Sultan Al; Tarapore, Phiroz E.; Cheung, Steven W.; Sabes, Jennifer H.; Chang, Jolie L.; Durr, Megan L. (OTO open : the official open access journal of the American Academy of Otolaryngology--Head and Neck Surgery Foundation, 2025)
Objective Traumatic brain injury affects 1.5 million people per year in the United States, with the majority classified as mild (mTBI). While many immediate symptoms are limited to the short‐term, some patients experience long‐term daily impairments in function and quality of life. The objective of this study was to assess the relationship between mTBI post‐concussive symptoms and hearing, tinnitus, and dizziness symptoms. Study design Cross‐sectional study. Setting Level I public trauma center. Methods Adult patients presenting with mTBI ≥6 months prior to study enrollment were asked to complete the Neurobehavioral Symptom Inventory (NSI), Revised Hearing Handicap Inventory (RHHI), Tinnitus Functional Index (TFI), and Dizziness Handicap Inventory (DHI) survey instruments. The NSI is a validated, self‐reported measure of post‐concussive symptoms. Linear regression analyses were performed. Results A total of 38 subjects were recruited, with mean age of 52 (range 24‐78), 74% male, 61% self‐identifying as White, and 87% self‐identifying as Non‐Hispanic/Latinx. Median time since injury was 32.5 months (IQR 30‐35). Mean NSI score was 22.32 (range 0‐70), mean RHHI was 16.05 (0‐68), mean TFI was 16.00 (0‐85.2), and mean DHI was 18.86 (0‐100). On linear regression, NSI score was positively correlated with RHHI, TFI, and DHI scores (P < .01). Conclusion The postconcussive symptoms of mTBI are associated with impairments in hearing, tinnitus, and dizziness. Based on this work, structural causal models may be developed to dissect associations to inform management and treatment of mTBI patients with audiovestibular symptoms.